Role of local actors in WASH (water, sanitation and hygiene) during disaster recovery: policy implications from evidence in Odisha, India. (7th August 2020) - Krishnan, Sneha; Twigg, John
ABSTRACT: There is a paucity of empirical insights on how existing policies in disaster recovery and water, sanitation and hygiene (WASH) play out during disaster recovery in the Global South. This paper addresses this critical gap using the case study of 2013 Cyclone Phailin in Odisha. The data was collected through participatory and learning action tools and semi-structured interviews with key informants. This study found pervasive exclusion of women and local actors from recovery decision-making. The policies and guidance at national and subnational level lacked clear emphases on roles and responsibilities of the local governments, and did not emphasise their role in setting recovery objectives and priorities. We conclude that existing policies should emphasise immediate as well as longer-term WASH needs, adopt a multi-hazard perspective in preparedness and WASH policies, and feature WASH during recovery in the existing manuals, policies and programmes.